Social Media Commercialization Influencers among Children and Youth: A Systematic Literature Review - Juwita Anindya; Irwansyah Irwansyah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Many uses of social media have now led to a lot of influential influencers in disseminating information and messages digitally. The information is also now widely addressed to children and adolescents. In fact, many children are already earning income as Social Media Influencers. Influencers are considered capable of having an impact on their followers through photo uploads and electronic word of mouth (eWOM) that they convey on their social media accounts. The research was conducted qualitatively with a literature review approach. The results show that the role of influencers has an impact on their followers among children and adolescents based on what they upload and what they write on their social media.